Vilna as a Centre of Hebrew Literature: The Journal Hazman - Holtzman , Avner (Colloquia, 2021)
In 1904, a Hebrew journalistic and literary initiative was established in Vilna, headed by the writer and publisher Ben-Avigdor, and the journalist and editor Ben Zion Katz. Vilna was chosen, among other reasons, for being a deeply rooted centre of Hebrew culture, with a long tradition of printing and publishing. The new initiative revived it as a magnet for Hebrew writers and journalists, an impressive team that joined together to create the daily Hazman (The Time) and its supplements. The editors’ policy was not to impose a binding political line on the paper, but to give an opening to all the factions in the Jewish public, while also hoping to expand the target audience of the paper. The year 1905 was the time of glory of Hazman, both for its news and its literary sections. But its momentum was halted during 1906, due to the political storm in Russia and the rapid decline of Hebrew journals, which lost most of their readership to the flourishing Yiddish press. Thus, the Hazman affair embodies a dramatic crossroads. It was the beginning of the decline of Hebrew literature in Eastern Europe, alongside the laying of the foundations for Hebrew literature in the Land of Israel during the first two decades of the 20th century. This essay draws an outline of the affair on the basis of a variety of sources, including the newspaper itself, memories of the personalities involved, and correspondence that has survived from those days.
Keywords: Vilna; Hazman; Romm printing house; Ben-Avigdor; Benzion Katz; Hebrew press